2015
DOI: 10.1590/1678-775720140473
|View full text |Cite
|
Sign up to set email alerts
|

The 19-bp deletion polymorphism of dihydrofolate reductase (DHFR) and nonsyndromic cleft lip with or without cleft palate: evidence for a protective role

Abstract: Objective Nonsyndromic cleft lip with or without cleft palate (NS-CL/P) are among the most common congenital birth defects worldwide. Several lines of evidence point to the involvement of folate, as well as folate metabolizing enzymes in risk reduction of orofacial clefts. Dihydrofolate reductase (DHFR) enzyme participates in the metabolic cycle of folate and has a crucial role in DNA synthesis, a fundamental feature of gestation and development. A functional polymorphic 19-bp deletion within intron-1 of DHFR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Our result was similar to the previous reported studies on Dutch and mixed UK populations (Van der Linden et al, ; Doudney et al, ), whereas a report from Irish population showed protective role of rs70991108 (Parle McDermott et al, 2007). It is assumed that rs70991108/19 bp deletion within intron 1 of DHFR affects the transcription and as well the translational process of the protein, however the direct role of the polymorphism is controversial (Rafighdoost et al, ). Extensive genetic and functional study is necessary to conclude the role of rs70991108 in NTD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our result was similar to the previous reported studies on Dutch and mixed UK populations (Van der Linden et al, ; Doudney et al, ), whereas a report from Irish population showed protective role of rs70991108 (Parle McDermott et al, 2007). It is assumed that rs70991108/19 bp deletion within intron 1 of DHFR affects the transcription and as well the translational process of the protein, however the direct role of the polymorphism is controversial (Rafighdoost et al, ). Extensive genetic and functional study is necessary to conclude the role of rs70991108 in NTD patients.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 288 subjects, including 132 NSCL/P and 156 healthy subjects, were recruited for this case-control study. The criteria for participants with NSCL/P and healthy individuals were previously described 22 - 24 . The local Ethics Committee of the Zahedan University of Medical Sciences approved the project (IR.ZAUMS.Rec.1393.6923) and informed consent forms were collected from all participants (or their legal guardians).…”
Section: Methodsmentioning
confidence: 99%
“…The interferon regulatory factor 6 (IRF6) gene is located on chromosome 1q32.2. It has been shown that variants of the IRF6 gene increased the risk of NSCL/P as well as tooth agenesis 20 , 22 , 26 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Parle-McDermott et al (2007), demonstrated that 19-bp deletion allele (D) may be a protective genetic factor against NTD by increasing DHFR mRNA levels in pregnant women. Moreover, a study by Rafighdoost also suggests that DHFR 19bp D/D genotype reduce the risk of Nonsyndromic cleft lip with or without cleft palate (NS-CL/P) in Iranian subjects (Rafighdoost et al 2015). Ongaro et al (2009) and Vagace et al (2011) reported that homozygosity for DHFR 19 bp deleted allele polymorphism has been associated with increased hepatotoxicity in leukemia patients treated with MTX.…”
Section: Germline Polymorphisms 1 Location: Intron 1 Polymorphismmentioning
confidence: 98%